Protection of Corporate Whistleblowers in the Digital Age: A Critical Analysis of Current Indonesian Frameworks - Tantimin, Tantimin; Hutauruk, Rufinus Hotmaulana; Tan, David (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Corporate whistleblowing plays a key role in ensuring transparency in Indonesian businesses. While the advent of digital technology can help improve the mechanism of corporate whistleblowing, this development still brings its own risks, particularly regarding the privacy of whistleblowers, which can significantly heighten risk of retaliations. This research aims to address the legal adequacy of Indonesia in ensuring the protection of corporate whistleblowers in the digital age, using normative legal research method and statutory approach. Findings of this research highlights the normative uncertainties and disharmony in the realm of witness protection, such as the lack of direct acknowledgement of corporate whistleblowers and the lack of supportive mechanism of digital corporate whistleblowing. In the digital context, there is a lack of mechanisms and compliance to address unique challenges that could arise in digital corporate whistleblowing, in the realm of data privacy. This research proposes a model of legal development consisting of key normative aspects that can be utilized to improve the relevant legal frameworks in Indonesia.